(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Tuberculosis (TB) is an infectious disease that is the main cause of death in developing countries and is the 3rd highest cause of death in the world. Behavioral factors that can influence the incidence of pulmonary TB in Lautem City include close contact with TB patients, alcohol use, smoking behavior, nutritional status, access to health care facilities, and family support. This study aimed to analyze the factors that influence the incidence of pulmonary TB in Lautem City, Timor Leste. This research is analytic observational with case control method. The number of case samples was 40 people. Data was collected through in-depth interviews using a structured questionnaire. Data were analyzed univariately, bivariate analysis using chi squared, and multivariate analysis using logistic regression. The results showed that the factors that influenced the incidence of TB in the Municipality of Lautem-Timor Leste were close contact with TB patients OR = 8,704; 95% CI = 2,390 – 31,699; p = 0.01), alcohol use, (OR = 4.702; 95% CI = 1.522-14.531; p = 0.007). Other factors that do not affect are access to health facilities, family support, nutritional status and smoking.For the results of the regression test the effect of consuming alcohol is 52%, close contact is 66.8% and if done simultaneously 90.49%. The factors that influence the incidence of pulmonary TB in the Municipality of Lautem Timor Leste are close contact with TB sufferers and alcohol use.